AND-1 fork protection function prevents fork resection and is essential for proliferation - Takuya Abe (Nature Portfolio, 2018)
AND-1, the vertebrate orthologue of Ctf4, is a critical player during DNA replication and for maintenance of genome integrity. Here the authors use a conditional AND-1 depletion system in avian DT40 cells to reveal the consequences of the lack of AND-1 on cell proliferation and DNA replication.